Tolstoy’s Philosophy of Non-Violence: A Discourse - UDOFIA, Christopher Alexander (Integrated Journal for Research in Arts and Humanities, 2023)
The title of this paper is Tolstoy’s Philosophy of Non-violence: A Discourse and the major thesis projected in this research is the idea that the actualization of peace, as demonstrated in Tolstoy’s philosophy of non-violence, requires the adoption of a revolutionary approach which has the potential of terminating the vicious circle of violence. Conflict is evidently an inevitable social phenomenon. Consequently, every event of conflict avails us of an opportunity to convert a seemingly destructive occurrence into a constructive outcome. This constructive conversion of conflict is what Tolstoy sought to achieve. This approach to conflict does not only ensure the sustenance of peace but it promotes harmonious social coexistence and entrenches the culture of non-violence. The benefits of non-violence cannot however be overemphasized and every pragmatic method for achieving peace should be studied. This constitutes the rationale behind this paper’s investigation of Tolstoy’s methodology of non-violence. Though most pundits would be aversed to the Tolstoyian method as impracticable, but Tolstoy was inspired by the example of Christ in the Bible and he believed that a passionate commitment to the Biblical teachings of Christ requires that Christians must imitate the examples of Christ. The paper utilizes the method of analysis to expose the conflict resolution formula of non-resistance to evil which is the intellectual ferment from which Tolstoy draws inspiration for his philosophy of non-violence. The major problem of this work is to expose the conflict resolution method espoused by Tolsoy and the central objective of the paper is to showcase the method of active passivism; borne out of the law of love, as an instrument of conquering violence in contradistinction to fascism which is based on the law of force and can only generate an unending spiral of violence. Whereas Tolstoy’s approach is contradictory to fascism in the sense that it absolutely negates the use of coercion and oppression, his non-violent non-resistance to evil is however a contrary to the non-violent resistance principle adopted by most freedom fighters like Gandhi and Martin Luther King Jnr. Tolstoy’s idea, critically assessed, may be appraised as containing the recipe for the multiplication of social evil; an outcome which Tolstoy vehemently aimed at averting and banishing through his modus operandi.